Simulating stress wave with flat-top partition of unity based high-order discontinuous deformation analysis - Liu, Xiaoying (2020)
Modelling the stress wave propagation in rock mass is a critical step to accurately assess the stability and damage of underground rock structures under dynamic loading. In this paper, the recently developed flat-top partition of unity (PU) based high-order approximation is coupled with Discontinuous Deformation Analysis (DDA) method to simulate stress wave propagation. In this method, the continuous blocks in DDA method are discretized by flat-top PU mesh, which is generated independently of the problem domain. High-order polynomials are employed as local displacement approximation to improve the numerical accuracy. Furthermore, non-reflective boundary is incorporated into this method to model the infinite problem domain. Numerical examples are presented and analyzed to verify the accuracy and efficiency of this method.